Effect of obesity and sociodemographic factors on chronic pain: a cohort study in general practice - Tatiana E. Morozova; Olga V. Vorob'eva; Anna A. Gertsog (ZAO "Consilium Medicum", 2023)
Background. Obesity is a component of metabolic syndrome, a separate disease, and a predictor of most chronic diseases. In recent decades, increasing attention has been paid to the effect of obesity on chronic localized pain. Aim. To determine the clinical characteristics of chronic localized pain depending on the body mass index and sociodemographic factors. Materials and methods. The study enrolled 112 eligible patients, 37 (33%) males and 75 (67%) females aged 19 to 65 years, with a mean age of 40 [32; 40] years. Patients were divided into three groups depending on the body mass index. All patients underwent a comprehensive general clinical examination, including an assessment of the pain prevalence and duration, the number of exacerbations in the current year, the pain severity using the Numeric Pain Rating Scale (NPRS), and the number of pain descriptors. Results. Obese patients experience more severe pain (p=0.004), are prone to prolonged (p=0.010) and frequent exacerbations (p=0.004), and use more lexical units to describe the pain (p=0.001). The main pain sites associated with obesity are the upper (p=0.023) and lower extremities (p=0.002). The overweight group falls between obese subjects and those with normal body weight and, by many parameters, is similar to the normal body weight group. It was noted that age worsens the pain; thus, with age, the number of exacerbations per year (p=0.006) and the duration of exacerbations (p=0.016) increase, and a direct correlation of age with the pain prevalence and the number of descriptors was revealed (r=0.271; p=0.004 and r=0.267; p=0.004, respectively). The most severe pain occurs in females. In contrast, physical activity reduces the number and duration of exacerbations and the prevalence of pain (p=0.004; p=0.048; p=0.015, respectively). Conclusion. Obesity, older age, and female gender are associated with more severe chronic pain. Body weight loss in obese patients with pain, as well as lifestyle modification with increased physical activity, is an essential aspect of overall rehabilitation, although additional studies are needed to establish strategies for maintaining long-term effects.